Love's wounds : violence and the politics of poetry in early modern Europe - Nazarian, Cynthia Nyree, 1980- (Cornell University Press, 2016)
"Investigates widespread metaphors of dismemberment, constraint, cannibalism, wounding, and tyranny in early modern French, English, and Italian literature. Through its comparative, inter-genre studies of Petrarch and five major Petrarchan poets of the sixteenth century, Love's Wounds shows how love poetry was actively transformed into a powerful tool for defining the nation and for reflecting on and shaping state authority"--